2011
DOI: 10.19030/jber.v3i6.2785
|View full text |Cite
|
Sign up to set email alerts
|

The Deterrents To CPE Effectiveness In The Accounting Profession: A Factor Analytic Study

Abstract: <p class="MsoNormal" style="text-align: justify; margin: 0in 0.5in 0pt;"><span style="font-size: 10pt;"><span style="font-family: Times New Roman;">This paper examines the effectiveness of CPE programs for accountants and whether there are deterrents that prevent some CPAs from getting the most out of their CPE hours.<span style="mso-spacerun: yes;">&nbsp; </span>Previous studies (Cross, 1981; Dao, 1975; Darkenwald &amp; Merriam 1982; Darkenwald &amp; Valentine, 1985, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…In light of study results, three barriers were found in which administrative barrier came up most prevalent barrier, work-related as more predictive and financial barrier as predicting barrier than the personal and family barrier. These results were congruent with other studies [12,[21][22][23]. Studies suggested that administrative favoritism based on personal relations or personal preferences which create big hindrance to nurses' participation in non-formal CNE activities.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In light of study results, three barriers were found in which administrative barrier came up most prevalent barrier, work-related as more predictive and financial barrier as predicting barrier than the personal and family barrier. These results were congruent with other studies [12,[21][22][23]. Studies suggested that administrative favoritism based on personal relations or personal preferences which create big hindrance to nurses' participation in non-formal CNE activities.…”
Section: Discussionsupporting
confidence: 89%
“…Concept of continuing education (CE) is emergent in both academic and daily practice [11]. Literature suggested that continuing medical education (CME) and continuing nursing education (CNE) is recognized worldwide by all health professionals [12]. Nurses are strongly encouraged to participate in CNE activities as a means of ensuring high quality care [13].…”
Section: Literature Reviewmentioning
confidence: 99%